Hamstring activation during lower body resistance training exercises - Ebben, W. P. (International Journal of Sports Physiology and Performance, 2009)
Purpose: The purpose of this study was to evaluate differences in hamstring activation during lower body resistance training exercises. This study also sought to assess differences in hamstring-to-quadriceps muscle activation ratios and gender differences therein. Methods: A randomized repeated measures design was used to compare six resistance training exercises that are commonly believed to train the hamstrings, including the squat, seated leg curl, stiff leg dead lift, single leg stiff leg dead lift, good morning, and Russian curl. Subjects included 34 college athletes. Outcome measures included the biceps femoris (H) and rectus femoris (Q) electromyography (EMG) and the H-to-Q EMG ratio, for each exercise. Results: Main effects were found for the H (P < 0.001) and Q (P < 0.001). Post hoc analysis identified the specific differences between exercises. In addition, main effects were found for the H-to-Q ratio when analyzed for all subjects (P < 0.001). Further analysis revealed that women achieved between 53.9 to 89.5% of the H-to-Q activation ratios of men, for the exercises assessed. In a separate analysis of strength matched women and men, women achieved between 35.9 to 76.0% of the H-to-Q ratios of men, for these exercises. Conclusions: Hamstring resistance training exercises offer differing degrees of H and Q activation and ratios. Women compared with men, are less able to activate the hamstrings and/or more able to activate the quadriceps. Women may require disproportionately greater training for the hamstrings compared with the quadriceps.